Variations in banana properties - Baini, R.; Langrish, T.A.G.; Rahman, M.R.; Ahmad Zauzi, N.S.; Abdul Rahman, N. (Springer Verlag, 2017)
Samples prepared from different bananas and from different parts of a banana may vary in their properties, which may cause variations in the final results in experiments. Therefore, assessment of variation in the samples’ properties is necessary, and it can be evaluated using statistical analysis. In this work, the variation in banana properties—colour, texture, moisture and sugar contents— within and between bananas were assessed statistically using a two-stage nested design test and the two-sample t-test. Results show that the variation of properties is significant for bananas with different degrees of ripeness. This finding suggests that samples can be prepared from different parts of the bananas provided that the bananas are at the same degrees of ripeness. It was also found that the location of sample in the drying chamber did not affect the measured properties of the drying bananas, significantly. The tests performed for banana texture using a laboratory apparatus produced results that were similar to those performed using a dynamic mechanical analyzer. This suggests that the use of highly-sophisticated instruments in the texture analysis of dried fruit in terms of the apparent modulus is not crucial.